Ajaran untuk Istri dalam Serat Patimah - Mirya Anggraeni (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The spiritual heritage of the nation of Indonesia is preserved on a variety of literary works, both native Indonesia values as well as values that come from outside, including the values of Islam. The arrival of Islam enriches the literary treasure in Java. At the moment it appears that works bersumberkan Islam. Among literary works such as the Javanese Islam Serat Patimah containing the advice of Prophet Muhammad to his daughter. In the text that a wife must respect her husband, loving husband, always serve the husband, and according to her husband. In addition, a wife should be respectful of the guest to maintain the good name of her husband. All advice is based on the teachings of Islam.